2004
DOI: 10.1111/j.0013-9580.2004.65203.x
|View full text |Cite
|
Sign up to set email alerts
|

NMDA Preconditioning Protects against Seizures and Hippocampal Neurotoxicity Induced by Quinolinic Acid in Mice

Abstract: Summary:Purpose: N-methyl D-aspartate (NMDA) preconditioning has been used to prevent cellular death induced by glutamate or NMDA in cultured neurons. Quinolinic acid (QA)-induced seizures are used to average NMDA receptors-evoked neurotoxicity in animal models. The purpose of this study was to investigate the potential neuroprotective effects of NMDA preconditioning against QA-induced seizures and hippocampal damage in vivo.Methods: Mice were pretreated with nonconvulsant doses of NMDA for different times bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
54
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 29 publications
4
54
0
1
Order By: Relevance
“…Experimental studies have evaluated the neuroprotective effects of preconditioning over seizures and neuronal loss (Kitagawa et al, 1990;Bortolotto et al, 1991;Sasahira et al, 1995;Najm et al, 1998;Andre et al, 2000;Zhang et al, 2002;Boeck et al, 2004;Andre et al, 2007;de Araujo Herculano et al, 2011;Xue et al, 2011). Most preconditioning studies used a subthreshold stimulus, followed by the same stimulus in a status epilepticus (SE)-inducing dosage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental studies have evaluated the neuroprotective effects of preconditioning over seizures and neuronal loss (Kitagawa et al, 1990;Bortolotto et al, 1991;Sasahira et al, 1995;Najm et al, 1998;Andre et al, 2000;Zhang et al, 2002;Boeck et al, 2004;Andre et al, 2007;de Araujo Herculano et al, 2011;Xue et al, 2011). Most preconditioning studies used a subthreshold stimulus, followed by the same stimulus in a status epilepticus (SE)-inducing dosage.…”
Section: Introductionmentioning
confidence: 99%
“…Most preconditioning studies used a subthreshold stimulus, followed by the same stimulus in a status epilepticus (SE)-inducing dosage. Examples of this preconditioning approach include subthreshold kainic acid (KA) injection or a short KA-induced seizure previous to KA-induced SE (Najm et al, 1998;Zhang et al, 2002), nonconvulsive NMDA treatment before quinolinic acid-induced SE (Boeck http et al, 2004;de Araujo et al, 2011) and one episode of bicuculline-induced seizure prior to a later bicucullineinduced seizure episode (Sasahira et al, 1995). Other studies used a preconditioning stimulus different from the SE-inducing stimulus, taking advantage of the cross-tolerance phenomenon, where an insult can induce tolerance from a later insult of different nature (Kirino, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…infusion in rats. In addition, Boeck et al (2004) showed that NMDA preconditioning promotes protection against QA-induced seizures and cell death.…”
Section: Introductionmentioning
confidence: 99%
“…scioncorp.com). The area where PI fluorescence (in pixels) was detectable above the background (damaged area of hippocampal slices) was analyzed using the ''density slice'' option of the Scioncorp software through the division of PI fluorescence by the total area of the slice [43].…”
Section: Preparation Of Hippocampal Slicesmentioning
confidence: 99%